Performance of an integrated multimodality image guidance and dose-planning system supporting tumor-targeted HDR brachytherapy for prostate cancer. (January 2022) - Grajales, David; Kadoury, Samuel; Shams, Roozbeh; Barkati, Maroie; Delouya, Guila; Béliveau-Nadeau, Dominic; Nicolas, Benedicte; Le, William Trung; Benhacene-Boudam, Mustafa-Karim; Juneau, Daniel; DaSilva, Jean N.; Carrier, Jean-Francois; et al.
Highlights: Image registration and EM tracking were integrated in a system for HDR brachytherapy. EM enabled use of partially visible catheters within image-validated implants. MRI-TRUS registration permits GTV projection over real-time TRUS for tumor-targeting. Elastic registration performs slightly better than rigid registration, but errors remain. Alignment of the urethral angle before deformation improved registration accuracy. Abstract: Background and purpose: Advances in high-dose-rate brachytherapy to treat prostate cancer hinge on improved accuracy in navigation and targeting while optimizing a streamlined workflow. Multimodal image registration and electromagnetic (EM) tracking are two technologies integrated into a prototype system in the early phase of clinical evaluation. We aim to report on the system's accuracy and workflow performance in support of tumor-targeted procedures. Materials and methods: In a prospective study, we evaluated the system in 43 consecutive procedures after clinical deployment. We measured workflow efficiency and EM catheter reconstruction accuracy. We also evaluated the system's MRI-TRUS registration accuracy with/without deformation, and with/without y-axis rotation for urethral alignment at initialization. Results: The cohort included 32 focal brachytherapy and 11 integrated boost whole-gland implants. Mean procedure time excluding dose delivery was 38 min (range: 21–83) for focal, and 56 min (range: 38–89) for whole-gland implants; stable over time. EM catheter reconstructions achieved a mean difference between computed and measured free-length of 0.8 mm (SD 0.8, no corrections performed), and mean axial manual corrections 1.3 mm (SD 0.7). EM also enabled the clinical use of a non or partially visible catheter in 21% of procedures. Registration accuracy improved with y-axis rotation for urethral alignment at initialization and with the elastic registration (mTRE 3.42 mm, SD 1.49). Conclusion: The system supported tumor-targeting and was implemented with no demonstrable learning curve. EM reconstruction errors were small, correctable, and improved with calibration and control of external distortion sources; increasing confidence in the use of partially visible catheters. Image registration errors remained despite rotational alignment and deformation, and should be carefully considered.